2020
DOI: 10.1055/a-1068-9260
|View full text |Cite
|
Sign up to set email alerts
|

QS ENDO Real – A Study by the German Endometriosis Research Foundation (SEF) on the Reality of Care for Patients with Endometriosis in Germany, Austria and Switzerland

Abstract: Endometriosis affects a significant number of young premenopausal women. Quite apart from the medical challenges, endometriosis is a relevant burden for healthcare and social security systems. Standardized quality indicators for the treatment of endometriosis have not previously been systematically verified. The three-stage study QS ENDO was initiated to record and improve the reality and quality of care. One of its aims is to create quality indicators for the diagnosis and treatment of endometriosis. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
0
11
0
7
Order By: Relevance
“…There is grayscale processing inside. Grayscale processing refers to the method of changing the gray value of each pixel in the source image point-to-point according to the transformation relationship based on specific target conditions [ 17 , 18 ]. In grayscale, in the RGB model, if R = G = B , the color represents a grayscale color.…”
Section: Comparison Of Endometriosis and Normal Endometriummentioning
confidence: 99%
“…There is grayscale processing inside. Grayscale processing refers to the method of changing the gray value of each pixel in the source image point-to-point according to the transformation relationship based on specific target conditions [ 17 , 18 ]. In grayscale, in the RGB model, if R = G = B , the color represents a grayscale color.…”
Section: Comparison Of Endometriosis and Normal Endometriummentioning
confidence: 99%
“…International and national guidelines recommend a histological assessment after surgical procedures to make a diagnosis of endometriosis 5 , 6 . An initiative to evaluate the quality of care in endometriosis centers in German-speaking countries in Europe was recently published 7 . It reported that all certified endometriosis centers took biopsies to confirm endometriosis histologically.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the current guidelines give no clear statements about the specific procedures for the histological assessment 5 , 6 . Standardized quality indicators for diagnosis and therapy have not been implemented to date 7 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bendifallah et al examined the correlation of surgeon and hospital caseloads of colorectal DE and the prevalence of major complications suggesting a critical optimal cut‐off of at least 20 procedures per center per year as a determining factor of surgical morbidity, 10 which is in line with recommendations for the surgical treatment of advanced ovarian cancer 11 . This has stimulated the ongoing process of establishing and certifying centers of excellence for treatment of extensive DE in Germany, Austria, the Czech Republic, Romania, Hungary and Switzerland primarily initiated by the Stiftung Endometrioseforschung following defined criteria and recommended caseloads for certain degrees of excellence and certification 12 . Hence, the aim of the present study was to evaluate the prevalence of major complications in certified tertiary referral centers for endometriosis and to examine a possible association between hospital caseload and the occurrence of grade III–IV complications following surgery for colorectal DE.…”
Section: Introductionmentioning
confidence: 87%
“… 11 This has stimulated the ongoing process of establishing and certifying centers of excellence for treatment of extensive DE in Germany, Austria, the Czech Republic, Romania, Hungary and Switzerland primarily initiated by the Stiftung Endometrioseforschung following defined criteria and recommended caseloads for certain degrees of excellence and certification. 12 Hence, the aim of the present study was to evaluate the prevalence of major complications in certified tertiary referral centers for endometriosis and to examine a possible association between hospital caseload and the occurrence of grade III–IV complications following surgery for colorectal DE.…”
Section: Introductionmentioning
confidence: 99%